Changes in floods and flood regimes in Canada - Donald H. Burn; Burn, Donald H.; Whitfield, Paul H. (2016)
Flood events in Canada result in larger costs, in terms of property damage, than any other natural disaster. Changes in land use, and more recently the impacts of climate change, can lead to changes in the flood regime. This paper describes research examining changes in the flood regime for watersheds across Canada. To distinguish between changes resulting from land-use changes and those occurring due to changes in climate, the analysis of flood data is conducted only on watersheds that are either part of a formal Reference Hydrologic Network (RHN), or which exhibit RHN-like characteristics. A total of 280 gauging stations have been analyzed for changes to a number of attributes of the flood regime. Changes in the magnitude and timing of flood events as well as the frequency and duration of high-flow events are examined for all 280 sites. Using all 280 sites and different groupings of the sites, based on timing of floods, drainage area and the RHN designation, changes were determined in the annual number ...
MAG ID: 2268559320

Changes to flood peaks of a mountain river: implications for analysis of the 2013 flood in the Upper Bow River, Canada - Whitfield, Paul H.; Pomeroy, John W. (Hydrological Processes, 2016)
The mountain headwater Bow River at Banff, Alberta, Canada was subject to a large flood in June 2013, over which considerable debate has ensued regarding its probability of occurrence. It is therefore instructive to consider what information long term streamflow discharge records provide about environmental change in the Upper Bow River basin above Banff. Though protected as part of Banff National Park, since 1885, the basin has experienced considerable climate and land cover changes, each of which has the potential to impact observations, and hence the interpretations of flood probability. The Bow River at Banff hydrometric station is one of Canada's longest operating reference hydrological basin network stations and so has great value for assessing changes in flow regime over time. Furthermore, the station measures a river that provides an extremely important water supply for Calgary and irrigation district downstream and so is of great interest for assessing regional water security. These records were examined for changes in several flood attributes and to determine whether flow changes may have been related to landscape change within the basin as caused by forest fires, conversion from grasslands to forest with fire suppression, and regional climate variations and/or trends. Floods in the Upper Bow River are generated by both snowmelt and rain-on-snow (ROS) events, the latter type which include floods events generated by spatially and temporally large storms such as occurred in 2013. The two types of floods also have different frequency characteristics. Snowmelt and ROS flood attributes were not correlated significantly with any climate index or with burned area except that snowmelt event duration correlated negatively to the Pacific Decadal Oscillation. While there is a significant negative trend in all floods over the past 100years, when separated based on generating process, neither snowmelt floods nor large ROS floods associated with mesoscale storms show any trends over time. Despite extensive changes to the landscape of the basin and in within the climate system, the flood regime remains unchanged, something identified at smaller scales in the region but never at larger scales.
MAG ID: 2519898953

Identification of changes in floods and flood regimes in Canada using a peaks over threshold approach - Burn, Donald H.; Whitfield, Paul H.; Sharif, Mohammed (Hydrological Processes, 2016)
Abstract Recent flood events in Canada have led to speculation that changes in flood behaviour are occurring; these changes have often been attributed to climate change. This paper examines flood data for a collection of 132 gauging stations in Canada. All of these watersheds are part of the Canadian Reference Hydrometric Basin Network (RHBN), a group of gauging stations specifically assembled to assist in the identification of the impacts of climate change. The RHBN stations are considered to have good quality data and were screened to avoid the influences of regulation, diversions, or land use change. Daily flow data for each watershed are used to derive a peaks over threshold (POT) dataset. Several measures of flood behaviour are examined based on the POT data, which afford a more in‐depth analysis of flood behaviour than can be obtained using annual maxima data. Analysis is conducted for four time periods ranging from 50 to 80 years in duration; the latter period results in a much smaller number of watersheds that have data for the period. The changes in flood responses of the watersheds are summarized by grouping the watersheds by size (small, medium, and large) and also by hydrologic regime (nival, mixed, and pluvial). The results provide important insights into the nature of the changes that are occurring in flood regimes of Canadian rivers, which include more flood exceedances, reduced maximum flood exceedance magnitudes for snowmelt events, and earlier flood events. Copyright © 2016 John Wiley & Sons, Ltd.
Keywords: Ouvrage_Collectif_Numéro1

The 2013 flood event in the South Saskatchewan and Elk River basins: Causes, assessment and damages - Pomeroy, John W.; Stewart, Ronald E.; Whitfield, Paul H. (2016)
In late June 2013, heavy rainfall and rapidly melting alpine snow triggered flooding throughout much of the southern half of Alberta. Heavy rainfall commenced on 19 June and continued for 3 days. When the event was over, more than 200 mm and as much as 350 mm of precipitation had fallen over the Front Ranges of the Canadian Rocky Mountains. Tributaries to the Bow River including the Ghost, Kananaskis, Elbow, Sheep and Highwood, and many of their tributaries, all reached flood levels. The storm had a large spatial extent causing flooding to the north and south in the Red Deer and Oldman Basins, and also to the west in the Elk River in British Columbia. Convergence of the nearly synchronous floodwaters downstream in the South Saskatchewan River system caused record high releases from Lake Diefenbaker through Gardiner Dam. Dam releases in Alberta and Saskatchewan attenuated the downstream flood peak such that only moderate flooding occurred in Saskatchewan and Manitoba. More than a dozen municipalities decla...
MAG ID: 2216829808

Flood processes in Canada: Regional and special aspects - Buttle, James M.; Allen, Diana M.; Caissie, Daniel; Davison, Bruce; Hayashi, Masaki; Peters, Daniel L.; Pomeroy, John W.; Simonovic, Slobodan P.; St-Hilaire, André; Whitfield, Paul H. (2016)
This paper provides an overview of the key processes that generate floods in Canada, and a context for the other papers in this special issue – papers that provide detailed examinations of specific floods and flood-generating processes. The historical context of flooding in Canada is outlined, followed by a summary of regional aspects of floods in Canada and descriptions of the processes that generate floods in these regions, including floods generated by snowmelt, rain-on-snow and rainfall. Some flood processes that are particularly relevant, or which have been less well studied in Canada, are described: groundwater, storm surges, ice-jams and urban flooding. The issue of climate change-related trends in floods in Canada is examined, and suggested research needs regarding flood-generating processes are identified.
MAG ID: 2298325701
Keywords: Ouvrage_Collectif_Numéro1